2008
DOI: 10.1002/mds.21974
|View full text |Cite
|
Sign up to set email alerts
|

Gait festination and freezing in Parkinson's disease: Pathogenesis and rehabilitation

Abstract: Freezing and festination during gait are common yet poorly understood motor control deficits in people with Parkinson's disease (PD). As a basis for evidence based clinical decision making during rehabilitation, we explore the underlying factors associated with freezing of gait in PD. It is argued that disorders of motor set and the sequence effect (festination) are associated with freezing, either in isolation or in combination. The contribution of environmental constraints, task related factors, attention, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 49 publications
3
54
0
5
Order By: Relevance
“…The vertical force traces showed that subjects were alternatively loading/unloading the legs but were unable to completely lift the feet off the ground. This phenomenon has been referred to as an underscaled bodyweight transfer [24][25][26] and has been observed during video analyses of trials in PD subjects walking with foot insoles and in the vertical accelerations of the shank [2,8,27]. It has been reported that these episodes present a complex motor pattern with higher frequency components than normal walking [8,27].…”
Section: Underscaled Repetitive Alternating Stepping May Provide Insimentioning
confidence: 97%
“…The vertical force traces showed that subjects were alternatively loading/unloading the legs but were unable to completely lift the feet off the ground. This phenomenon has been referred to as an underscaled bodyweight transfer [24][25][26] and has been observed during video analyses of trials in PD subjects walking with foot insoles and in the vertical accelerations of the shank [2,8,27]. It has been reported that these episodes present a complex motor pattern with higher frequency components than normal walking [8,27].…”
Section: Underscaled Repetitive Alternating Stepping May Provide Insimentioning
confidence: 97%
“…These gait problems include reduced or absent arm swing, shuffling steps, reduced stride length leading to an overall reduction in walking velocity [26,31], slower turning [54], balance problems [7], festination (an accelerating series of short steps while leaning forwards) [32], and freezing of gait (FoG) during which effective walking ceases temporarily and the patient feels as if their feet are 'glued to the floor' [15][16][17]. These gait problems in PD increase the risk of falls and the associated fear of falling (FoF) can influence daily activities, especially those that involve venturing outside the home [41].…”
Section: Introductionmentioning
confidence: 99%
“…Further supporting the role of diverse and nondopaminergic circuitry in the mechanism of FOG, visual and auditory cueing strategies have been reported to ameliorate FOG and other gait deficits in patients with PD [8][9][10][11][12]. High-contrast, transverse line visual cues on the floor have been found to improve stride length and velocity, among other measures, in patients with PD in several trials, one of which also demonstrated reduced FOG episodes [11,[13][14][15][16][17][18].…”
Section: Freezing Of Gait (Fog) Is a Disabling Phenomenon That Affectmentioning
confidence: 97%